The effects of an educational program based on modeling and social stories to improve the social skills of students with autism - Alkinj, Issa Jamil Qasim (2021)
Social communication difficulties are one of the most common issues among individuals with autism spectrum disorder, affecting their social and academic life, and isolating them from their environment. The current study was aimed to examine the effectiveness of an educational program to improve the social communication skills of a sample of six high functioning students with autism at the Autism Academy of Jordan. The program consisted of 12 sessions based on multiple strategies including social stories, video modeling, and video selfmodeling targeting several social reciprocity skills. The mixed method (quantitative and qualitative) was used to examine the impact of the program on the experimental group. The results of the Mann -Whitney test demonstrated that all participants in the experimental group achieved significant improvements on the post-test of the Autism Social Skills Profile (ASSP) in both domains of social reciprocity, and social participation skills over the monitoring group. Further, the data from teachers’ interviews, analyzed using WebQDA software, corroborated the results about the significant improvements in social skills after the intervention of the educational program. The implications of the study for psychological and educational intervention are mentioned, as well as suggestions for research aimed at promoting the personal and social development of individuals with Autism Spectrum Disorder.